TCAD and EM co-simulation method to verify SiGe HBT measurements up to 500 GHz. (December 2020) - Panda, Soumya Ranjan; Fregonese, Sebastien; Deng, Marina; Chakravorty, Anjan; Zimmer, Thomas
Highlights: A systematic method for the verification of high frequency measurement (up to 500 GHz) of silicon germanium heterojunction bipolar transistor (SiGe HBT) is proposed. Merits and demerits of different calibration techniques are discussed, On-wafer TRL calibration is chosen for such high frequency. Setup for High frequency measurement up-to 500 GHz, SiGe HBT calibration in TCAD and corresponding back-end-of-line using EM simulations are discussed in detail. Impact of errors in calibration and de-embedding on amplifier circuit design is presented. Abstract: A systematic method for the verification of high frequency measurement (up-to 500 GHz) of silicon germanium heterojunction bipolar transistor (SiGe HBT) is proposed. First of all, the method involves an accurate estimation of the effects of passive environment on the overall measurement by a detailed electro-magnetic (EM) simulation. This ensures that the complete measurement environment like probes, pads and access lines along with the appropriate layouts are precisely included in the EM simulation framework. In order to additionally include the active device like SiGe HBTs, technology computer aided design (TCAD) tool is used to simulate the device S -parameters. TCAD simulation results are fed into an EM-plus-SPICE simulation framework to emulate a complete on-wafer measurement environment. The final simulation results show appreciable correlation with the on-wafer measurement data up-to 500 GHz.